2000
DOI: 10.1063/1.1321045
|View full text |Cite|
|
Sign up to set email alerts
|

An intramolecular theory of the mass-independent isotope effect for ozone. II. Numerical implementation at low pressures using a loose transition state

Abstract: A theory is described for the variation in the rate constants for formation of different ozone isotopomers from oxygen atoms and molecules at low pressures. The theory is implemented using a simplified description which treats the transition state as loose. The two principal features of the theory are a phase space partitioning of the transition states of the two exit channels after formation of the energetic molecule and a small ͑ca. 15%͒ decrease in the effective density of states, ͓a ''non-Rice-Ramsperger-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
112
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 59 publications
4
112
0
Order By: Relevance
“…It was shown [1][2][3] that the unusual mass-independent isotope effect in ozone formation [4][5][6] can be explained by assuming some non-RRKM ͑non-Rice-Ramsperger-KasselMarcus͒ behavior of energetic ozone molecules. The reader can find a review of literature on the ozone isotope effect and the current status of theoretical investigations in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown [1][2][3] that the unusual mass-independent isotope effect in ozone formation [4][5][6] can be explained by assuming some non-RRKM ͑non-Rice-Ramsperger-KasselMarcus͒ behavior of energetic ozone molecules. The reader can find a review of literature on the ozone isotope effect and the current status of theoretical investigations in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The non-RRKM behavior of vibrationally excited ozone molecules was suggested in several classical mechanical numerical studies and an important role of the coupling of the rotational degrees of freedom to the vibrations was emphasized. 7,8 Recently, the classical molecular dynamics ͑MD͒ simulations 9,10 of collisional ozone formation O + O 2 → O 3 ‫ء‬ showed a nonstatistical distribution of lifetimes of the vibrationally excited ozone molecules. In a series of two papers we show analytically that the observed non-RRKM effects are indeed governed by the Coriolis coupling between the rotational and vibrational degrees of freedom, which cannot be accounted for by the standard RRKM theory.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Rice-RamspergerKassel-Marcus ͑RRKM͒ theory with a master equation approach for the collisional deactivation of the intermediate excited ozone molecules has been applied to study both phenomena. [32][33][34] It was found that the MIF can be explained when an -effect, a non-RRKM effect, [30][31][32][33][34] which reduces dynamically the low-pressure rate constant of the recombination to form symmetric molecules by a factor of compared to that for the asymmetric ones, and a weak collision effect [32][33][34] for the deactivation of excited ozone molecules is also included in the theory. For the unusually large massdependent isotope effect, observed under very special ͑"unscrambled"͒ experimental conditions, the zero-point energy differences in the two dissociation paths of any asymmetric XYZ * isotopomer play the key role, together with the weak collision efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Our interest in the subject was prompted by studies of ozone whose formation and isotopic effects have been of much recent interest. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In general, the formation of a molecule AB is described by A + B AB ‫ء‬ , ͑1͒…”
Section: Introductionmentioning
confidence: 99%